Formulation of Sustained-Release Tablets of Tolperisone HCl Using Different Blends of Hydrophilic and Hydrophobic Polymers - Butola, Mansi; Badola, Ashutosh; Nainwal, Nidhi; Rana, Shilpa; Jakhmola, Vikash; Ale, Yogita; Ansori, Arif N. M. (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Tolperisone Hydrochloride (HCl) is a muscle relaxant that relaxes muscles by acting on the Central Nervous System (CNS). It acts at the spinal cord level by blocking calcium and sodium channels. It primarily inhibits transmitter release from primary afferent terminals through pre-synaptic inhibition via simultaneous action on voltage-gated sodium and calcium channels. Its elimination half-life t is 1.5 to 2.5 hr. To maintain a constant plasma concentration, conventional Tolperisone HCl tablets are administered multiple times in divided dosages, which results in patient noncompliance. This problem can be overcome by preparing Tolperisone HCl sustained-release tablets. Materials and Methods Tolperisone HCl sustained release matrix tablet was prepared by utilizing the wet granulation method with Hydroxypropyl Methylcellulose (HPMC K100) and Ethyl Cellulose (EC) in combination at different ratios. Evaluation: The powdered blend was evaluated for adequate flow properties using Carr’s compressibility index, tapped density, bulk density, angle of repose, and Hausner’s ratio before compression. The compressed tablets were then further evaluated for diameter, friability, content uniformity, thickness, hardness, weight variation, and in vitro drug release. Results The drug release study showed that HPMC K100 and EC in combination were able to sustain the drug release in acid buffer pH 1.2 for the first 2 hr, followed by phosphate buffer pH 6.8 for the next 12 hr. It is also suggested that if the amount of ethyl cellulose increases, drug release decreases because ethyl cellulose is a water-insoluble polymer. All the formulations show drug release for more than 12 hr.
Keywords: Tolperisone HCl; Muscle Relaxant; Sustained Release; HPMC K100; Ethyl Cellulose